2023
DOI: 10.24820/ark.5550190.p011.949
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic strategies of pyridazino[4,5-b]indoles

Abstract: Pyridazino [4,5-b]indole is an important class of heterocyclic compounds with numerous applications in the field of medicinal chemistry. This review summarizes the synthetic methods of pyridazino [4,5-b]indoles published during the period from 1962 to 2022. In this review, we have discussed different methods for the synthesis of pyridazino [4,5-b]indole from various starting materials and the difficulties that scientists faced during the preparation process. We focus on the recent developments in synthetic met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The recently synthesized compounds' antibacterial efficacy was also assessed. The results indicated that some of these compounds have moderate activity towards bacteria [8]. As part of our research, we are interested in construction of new synthetic pathways for a range of quinazolinone substrates that have interesting biological and pharmacological properties [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], In this article, we provide a report.…”
Section: Introductionmentioning
confidence: 99%
“…The recently synthesized compounds' antibacterial efficacy was also assessed. The results indicated that some of these compounds have moderate activity towards bacteria [8]. As part of our research, we are interested in construction of new synthetic pathways for a range of quinazolinone substrates that have interesting biological and pharmacological properties [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], In this article, we provide a report.…”
Section: Introductionmentioning
confidence: 99%